M. M. Bakhtin in Russian Culture of the Twentieth Century (Translated by Ann Shukman) - M. L. Gasparov (Studies in 20th & 21st Century Literature, 1984)
This article by M.L.Gasparov was first published at Tartu in the Soviet Union in 1979 and has been translated and edited here with notes by Ann Shukman. Gasparov emphasizes four aspects of Bakhtin's thought: "his zeal for expropriating 'the other's word' "; "his zeal for dialogue"; "a nihilistic selection of values"; "the opposition of the novel to poetry." Ann Shukman's commentary places Gasparov's article in context.
Keywords: M.L.Gasparov; Ann Shukman; translated; translation; Bakhtin; nihilism; poetry; dialogue